EFEK MEDIASI KEPUASAN KERJA DAN PENGARUH STRES KERJA TERHADAP KINERJA - Thomas Aquinas Radito; Nerys Lourensius L T; Ismail Mursidi; Meniek Srining Prapti (Jurnal Solusi, 2022)
This study aims to examine and analyze the role of job satisfaction in mediating the effect of job stress on employee performance. The research was conducted on permanent employees of Tk Hospital. III 04.06.03 Dr. Soetarto Yogyakarta. 150 respondents were used as the sample. The role of mediation will be tested by comparing the direct effect of job stress on performance with the effect of job stress on employee performance by including job satisfaction as an independent variable. Testing using Regression analysis. The results showed that when the Job Satisfaction variable was included as an independent variable, the effect of the Job Stress variable which was previously significant became insignificant. The decrease in the value of the B coefficient from 0.360 to 0.191 and the significance value which was originally significant at 0.001 to not significant at 0.054 indicates that the Job Satisfaction variable fully mediates the effect of work stress on performance